Analysing the importance of governance, politics and energy consumption on environmental sustainability in India - Shambhu Rout; Namitarani Gochhayat (Discover Sustainability)
Abstract Environmental sustainability is a key issue in the current economic situation. Political and governance factors play an important role in formulating good environmental policy. This paper investigates the effect of governance, political stability, and energy consumption on per capita greenhouse gas (GHG) emissions as a measure of environmental sustainability. Using data from 1996 to 2021 and employing the ARDL model, this study found that governance has improved environmental quality by reducing GHG emissions in India. The governance variables contributing to this improvement include government effectiveness, regulatory quality, and accountability. In contrast, energy consumption and corruption levels positively affect GHG emissions. Political stability shows a long-term positive effect on GHG emissions and supports environmental sustainability. Further, this study shows that governance instruments are sustainable in the long run, whereas energy consumption positively affects GHG emissions in both the short and long run. GHG emission per capita is also responsible for the further spreading of emission levels in the long run.